Fingerprint Acquisition Based on Photo‐Thermal Coloration of MoO3 Ceramic upon the Irradiation of Multiband Light outside the Bandgap. Issue 11 (6th September 2020) - Li, Mingjun; Yang, Zhengwen; Wen, Yugeng; Ruan, Jiufeng; Ren, Youtao; Qiu, Jianbei; Song, Zhiguo; Wang, Yuehui; Liu, Bitao
Abstract: Fingerprints acquisition for identity recognition is extensively studied as a high requirement of the development of fingerprint acquisition technology. The photochromism of MoO3 is widely reported upon ultraviolet light irradiation inside the bandgap, and if the photochromism can be achieved outside the bandgap, then the discoloration adjustment can be more diversified and the application range will be wider. However, there are no report of the photochromism of MoO3 upon the irradiation of multiband light outside bandgap. Herein, the MoO3 ceramic is prepared by the solid‐state reaction, and its photochromism is investigated upon the irradiation of multiband light outside the bandgap. The colors of MoO3 ceramic change from grey to dark blue upon the 473, 532, 808, or 980 nm laser irradiation, and the dark blue of MoO3 ceramic is bleached upon thermal stimulation. The photochromic mechanism of MoO3 ceramic is attributed to the laser‐induced heat effect. For the first time, fingerprint acquisition is obtained by means of the photo‐thermal‐chromism of MoO3 ceramic. The cycle experiment demonstrates that the fingerprint acquisition based on the photo‐thermal‐chromism of MoO3 has excellent repeatability and stability. These results suggest that this technology is nondestructive and repeatable, opening up a new approach for fingerprint acquisition. Abstract : The photo‐thermal‐chromism of MoO3 is achieved by the irradiation of multiband light outside the bandgap, and colors of MoO3 ceramic change from grey to dark blue upon the 473, 532, 808, or 980 nm laser irradiation. Based on the photo‐thermal‐chromism phenomenon outside the bandgap, a new fingerprint acquisition method is realized, and the process owns remarkable reversibility and repeatability.